Farming practices of Litopenaeus vannamei: An empirical study in West Bengal, India - Maity, Animesh; Saha, Biswarup; Pandit, Arun; Patra, Pranab (Journal of the Inland Fisheries Society of India, 2021)
Introduction of shrimp species Litopenaeus vannamei has brought a sea change in Indian shrimp production and processing industry. Culture of white-leg shrimp farming is gaining popularity in most areas in West Bengal. Culture of L. vannamei in West Bengal covers an area of 4,127 ha with 22,191 MT production in the year 2017-18. For the present study on different farming practices of this species a total of 200 shrimp farmers were selected through simple random sampling method. The data were collected mainly by interview with the help of structured interview schedules. However observation was also an important source of information. It was found that around 63% of the farmers cultured two crops a year, and 88% of them practiced L. vannamei farming intensively. Around two-third of total respondents maintained an average 4.5-6 ft pond depth. Majority (71.5%) of the shrimp farmers followed medium level of stocking density between 53 and 71 nos. PL m-2 and more than half (54%) of the respondents used to manage their farms on hired labour as well as own family labour. Total cycle of culture period was between 90 and 130 days in all the cases. Average pH of the farming ponds ranged between 7.5 and 8.5, average D.O. of 4-6 mg l-1, and average salinity of 9-11 ppt. The shrimp production ranged between 1 and 12 tonnes/acre depending upon stocking density, growth rate and mortality levels. Though all the sampled farmers applied for registration of their farms for shrimp production, only 28% of them got their registration from the Coastal Aquaculture Authority. Key words Litopenaeus vannamei; Culture period; Pond conditions; Production; West Bengal